Increased daytime and awakening salivary free aldosterone in essential hypertensive men - Gideon, Angelina; von Känel, Roland; Degroote, Cathy; Thomas, Livia; Zuccarella-Hackl, Claudia; Wiest, Roland; Wirtz, Petra H. (Frontiers in Cardiovascular Medicine, 2024)
Background: While aldosterone plays an important role in blood pressure regulation, its role in essential hypertension (EHT) remains unclear. Here, we systematically investigated the secretion of biologically-active free aldosterone in saliva in response to awakening (AldAR) and during the day (AldDay) in EHT compared to normotensive controls (NT).In 30 men with EHT and 30 age-matched NT, AldAR saliva samples were collected immediately after awakening and 15, 30, 45, and 60 min thereafter and AldDay samples were collected from 08:30-22:00 h on two consecutive days.Results: Over the course of the day, men with EHT had higher repeated AldDay levels compared to NT (p = .002) with higher concentrations in the morning hours (p's ≤ .047), a steeper decline over the course of the day (p's ≤ .018), and similar concentrations in the evening (p's ≥ .21). Regarding AldAR, we observed higher concentrations in EHT at awakening (p = .017) and borderline higher concentrations at 15 min (p = .086). No differences were found 30-60 min after awakening (p's ≥ .34). Analyses with repeated and aggregated AldAR levels resulted in borderline significantly higher free aldosterone in EHT (p's ≤ .077). Complementary analyses confirmed linear associations between higher blood pressure and higher AldAR and AldDay levels.Conclusions: Our data point to elevated salivary free aldosterone secretion in EHT over the course of the day, particularly in the morning hours. As the free aldosterone fraction is considered biologically active, our data may point to a biological mechanism underlying EHT.